KEBIJAKAN PENDIDIKAN BERBASIS KARAKTER DALAM MENINGKATKAN MORALITAS PESERTA DIDIK DI ERA DIGITAL - Rina Wijaya; Siti Nuraini (Jurnal Dinamika Pendidikan Islam, 2026)
The digital era presents serious challenges to students' morality due to negative content exposure and weakening character values. This study aims to analyze the implementation of character-based education policies in improving the morality of students in the digital era. The method used is a systematic literature study with a qualitative-descriptive approach, examining various character education policies and regulations in Indonesia. The results show that character-based education policies embodied in the Minister of Education Regulation and Character Education Strengthening (PPK) programs are effective in improving student morality when implemented consistently and integrated with digital technology. The study concludes that synergy between policy, teachers, families, and a healthy digital environment is the key to successful character formation in students.